MODEL PEMBERDAYAAN PEREMPUAN DESA WISATA KAMPUNG BAJO BERBASIS KOMUNITAS DI KELURAHAN ANAWOI KECAMATAN TANGGETADA KABUPATEN KOLAKA - I Rawati; Fetni; Puji Prio Utomo; Mardiana (Journal Publicuho, 2025)
This study aims to examine women's empowerment in the management of community-based Bajo Village tourism villages in Anawoi Village, Tangketada District, Kolaka Regency. The research design uses a qualitative approach with a case study method involving in-depth interviews, focus group discussions (FGD), and participatory observation. The results of the study indicate that women in Bajo Village have an important role in the tourism sector, especially in managing homestays, providing culinary delights, and making handicrafts. However, women's involvement in strategic decision-making related to the development of tourism villages is still limited. The main obstacles faced are social norms that limit women's roles, lack of access to capital and training, and limitations in business management. Therefore, this study proposes a community-based empowerment model that can improve women's skills and strengthen their participation in tourism management, as well as provide access to greater resources. The recommendations from this study are the need for skills training, strengthening social networks, and support from the government to create an ecosystem that supports women's empowerment in tourism villages.